A new enzyme-free quadratic SERS signal amplification approach for circulating microRNA detection in human serum. Issue 90 (24th September 2015) - Zheng, Jing; Ma, Dandan; Shi, Muling; Bai, Junhui; Li, Yinhui; Yang, Jinfeng; Yang, Ronghua
Abstract : In this communication, we proposed a new enzyme-free quadratic SERS signal amplification approach for the ultrasensitive detection of circulating miRNA in human serum. Abstract : In this communication, we proposed a new enzyme-free quadratic SERS signal amplification approach for the ultrasensitive detection of circulating miRNA in human serum. Combined with miRNA-triggered hybridization chain reaction and Ag + -mediated cascade amplification, a limit of miRNA detection as low as 0.3 fM could be achieved. More importantly, our method is suitable for the direct detection of circulating miRNAs in human serum collected from patients with different stages of chronic lymphocytic leukemia (CLL).